Mothers' perceptions of their premature infant's communication: A description of two cases - Michelle Pascoe; Divya Bissessur; Pat Mayers (AOSIS, 2016)
Background: Survival rates of premature infants have increased due to advances in medicine. Premature infants however, remain at risk for developmental delays including communication difficulties. The bonding and attachment experiences of premature infants and their parents are often challenged, further placing these infants at risk for communication difficulties. This study firstly aimed to explore mothers' perceptions of their premature infants' communication. The second aim was to explore the mothers' perceptions of their own role in the communication development of their infants. Methods: A descriptive, longitudinal study was conducted with two mother-infant dyads. Three visits took place in the first year of life. Subjective maternal reports were obtained through semi-structured interviews. Results: Differences in the two mothers' perceptions were noted. The mothers described helping their infants to communicate through physical contact and talking. Risk and protective factors for early communication development are discussed in relation to the findings. Conclusion: The findings support the need for a healthy mother-infant relationship in the first few months of life. Health professionals should support premature infants and their families after discharge in order to help them interact with their infants and encourage attachment and bonding.